1999
DOI: 10.1016/s0005-2728(99)00049-3
|View full text |Cite
|
Sign up to set email alerts
|

The plasma membrane NADH oxidase of HeLa cells has hydroquinone oxidase activity

Abstract: The plasma membrane NADH oxidase activity partially purified from the surface of HeLa cells exhibited hydroquinone oxidase activity. The preparations completely lacked NADH:ubiquinone reductase activity. However, in the absence of NADH, reduced coenzyme Q10 (Q10H2=ubiquinol) was oxidized at a rate of 15+/-6 nmol min-1 mg protein-1 depending on degree of purification. The apparent Km for Q10H2 oxidation was 33 microM. Activities were inhibited competitively by the cancer cell-specific NADH oxidase inhibitors, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 30 publications
3
63
0
1
Order By: Relevance
“…Although externally-supplied NADH was used to assay ENOX activity, hydroquinones resident in the plasma membrane are most likely the natural substrate [10]. When reduced coenzyme Q 10 was assayed, two sets of oxidative maxima were seen (Figure 4) similar to those observed with NADH (Figure 1).…”
Section: Hydroquinone Oxidationmentioning
confidence: 90%
See 2 more Smart Citations
“…Although externally-supplied NADH was used to assay ENOX activity, hydroquinones resident in the plasma membrane are most likely the natural substrate [10]. When reduced coenzyme Q 10 was assayed, two sets of oxidative maxima were seen (Figure 4) similar to those observed with NADH (Figure 1).…”
Section: Hydroquinone Oxidationmentioning
confidence: 90%
“…10 7 cells in 50 µl) were combined with 2.5 ml 50 mM Tris-Mes buffer (pH 7.0), 2 mM KCN and 150 µM NADH. To refold and renature the ENOX proteins of the heat-inactivated yeast, reduced glutathione (GSH) was added to a final concentration of 100 µM, and incubated for 10 min to reduce disulfides to allow for refolding.…”
Section: Nad(p)h Oxidase Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Macho et al (1999) showed that capsaicin-induced apoptosis was correlated with the level of PMOR activity in different cell types. Capsaicin acts as a competitive inhibitor of ubiquinone (Kishi et al 1999) and perturbs electron flow to oxygen via the plasma membrane NADH oxidase, which normally produces water . Similarly, we found that capsaicin appears to inhibit CoQ 1 -dependent FeCN reduction by chick neurons, although non-specific interference with the assay makes it difficult to collect reliable data.…”
Section: Discussionmentioning
confidence: 99%
“…An isoform of NADH-cytochrome b 5 reductase (EC. 1.6.2.2) located on the cytoplasmic surface of the plasma membrane reduces ubiquinone and distinct NADH oxidase and FeCN reductase activities use electrons from hydroquinone to reduce oxygen, forming water (Kishi et al 1999), or to reduce FeCN (Kim et al 2002). This ubiquinone-mediated system has yet to be identified in neurons.…”
mentioning
confidence: 99%